Tensile stiffness of perfobond rib connectors in steel–concrete composite pylon of bridges. (1st June 2023) - Sun, Lipeng; Liu, Yongjian; Wang, Haitao; Shi, Fengrong; Liu, Jiang; Jiang, Lei
Highlights: Tensile stiffness of PBLs in composite pylons is experimentally and numerically studied. Perforated rib's geometric properties significantly affect tensile stiffness of PBLs. Increasing concrete strength increases tensile stiffness of PBLs. Proposed analytical spring model accurately predicts tensile stiffness of PBLs. Abstract: Perfobond rib connectors (PBLs) are subjected to considerable tensile forces when used as stiffeners in steel panels and force-transfer structures in the cable anchorage zone in the steel–concrete composite pylons of cable-stayed bridges. Determining the elastic tensile stiffness of the PBLs is necessary for a structural analysis of the composite pylons. This investigation aimed to explore the critical parameters affecting the elastic tensile stiffness of PBLs and propose equations for accurately predicting the tensile stiffness of PBLs. Twelve PBL specimens were tested under pull-out load to investigate their elastic tensile stiffness. Thereafter, a parametric analysis was conducted via the finite element approach to examine the influence of the geometric characteristics of the perforated rib, transverse rebar diameter, and concrete strength on the tensile stiffness of the PBL. The results demonstrated that the elastic tensile stiffness of PBLs increased with the increase in the rib thickness, hole diameter, and concrete strength but decreased with increasing embedded depth. The perforated rib width had no influence on the elastic tensile stiffness. Additionally, the elastic tensile stiffness increased slightly as the transverse rebar diameter increased. Subsequently, a theoretical spring model was developed to predict the elastic tensile stiffness of the PBLs, considering the contribution of perforated ribs and concrete dowels. Finally, a comparative analysis was performed, which proved that the proposed equations in the present study based on the spring model were accurate in predicting the tensile stiffness of PBLs. The proposed equations are recommended for application in the structural analysis of composite pylons.